Nonmetastatic cell 1 gene polymorphisms are associated with the clinical progression and prognoses of patients with colorectal cancer - Liu, Yabin; Bai, Tianliang; Zhang, Zhenxi; Xu, Yanjun; Kong, Dexian (Frontiers in Genetics, 2025)
BackgroundGenetic polymorphisms in the nonmetastatic cell 1 gene (NME1) are reportedly associated with the risk of various tumors and the prognoses of cancer patients. The aims of this study were to evaluate the contribution of two polymorphisms of NME1 to the risk of colorectal cancer (CRC) development and the clinical outcomes of CRC patients in a northern Chinese population.MethodsThis study included 453 CRC patients and 464 controls. Genotyping of two polymorphisms (rs2302254 and rs16949649) in the promoter region of NME1 was performed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method.ResultsThe results revealed that the rs2302254 and rs16949649 polymorphisms were not associated with the risk of CRC. However, the rs2302254 TT mutant genotype was associated with an increased risk for advanced clinical stage and lymph node metastasis. Moreover, survival analysis revealed that patients with the homozygous mutant TT genotype of rs2302254 had significantly shorter disease-free survival (DFS) and overall survival (OS) times than patients with the homozygous wild-type CC genotype.ConclusionThe rs2302254 polymorphism might function as a potential molecular marker for predicting the progression and prognosis of CRC.